Cuentas por cobrar de la Empresa Agrícola Comercial Dos Hermanos S. A, de la provincia de Los Ríos en la cuidad de Quevedo en el periodo 2022-2023. - Miranda Jiménez, Nohemi Nicole (2024)
Accounts receivable are one of the most fluid sources of money that an economic activity can have. The objective is to analyze the management of accounts receivable of the company AGRÍCOLA COMERCIAL DOS HERMANOS S. A, of the city of Quevedo, Province of Los Ríos in the periods 2022-2023. The methodological framework of the research has a qualitative and quantitative approach; that is, mixed, non-experimental, non-cross-sectional design. The types of research that was applied were descriptive, documentary and field. The techniques used are: interview and documentary review. The results of the investigation allowed us to conclude that: The weaknesses of the registration of accounts receivable of the company AGRÍCOLA COMERCIAL DOS HERMANOS S. A, of the city of Quevedo, Province of Los Ríos in the periods 2022-2023 are: no account with clearly defined policies, strategies or procedures to carry out an effective collection process, financial analyzes are not carried out, the accounting record of accounts receivable does not fully comply with what is established by international financial reporting standards. It is recommended that the company AGRÍCOLA COMERCIAL DOS HERMANOS S. A, develop and implement clear and concise credit and collection policies so that an effective collection process can be carried out that helps mitigate the presence of an increase in outstanding accounts collection.